Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

anonnnn

  • 3 years ago

Help? Explain? 3x - 9y = 3 6x - 3y = -24

  • This Question is Closed
  1. sgta101
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    These are linear equations what did you want to do with them?

  2. anonnnn
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    It's a system, I have to solve them but I can't figure out how to do it.

  3. yummydum
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 4

    you can solve using elimination: multiply the first equation by 2 to eliminate the x's:\[~~~~~2~(3x-9y=3)~~~~~~\implies~~~~~~~~6x-18y=6\]\[\underline{-~(6x-3y=-24)}~~~~~\implies~~-\underline{(6x-3y=-24)}\]\[~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~0-15y=30\]now solve for y:\[-15y=30\]divide by -15:\[y=-2\] knowing the value of y we could now use substitution to solve for x: pick either of the two equations and plug in the value of y\[3x-9(-2)=3\]distribute:\[3x+18=3\]subtract 18:\[3x=-15\]divide by 3:\[x=-5\] so: \(x=-5\) and \(y=-2\) hope this helps! :)

  4. anonnnn
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    So much! You helped me understand it better too, thank you so much!

  5. yummydum
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 4

    No problem, anytime! :)

  6. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy